Pelatihan Digital Marketing Hotel Mengunakan Teknologi RedDoorz Sebagai Potensi Bisnis - Jimmy Nganta Ginting; Pretty Naomi Sitompul; Mei Veronika Sri Endang Siagian; Sastra Wandi Nduru; Febrina Soraya Tanjung (Universitas Mandiri Bina Prestasi (UMBP), 2023)
The application of the RedDoorz application technology is one of the sustainable hospitality tourism digital marketing innovations and is naturally carried out in North Sumatra Province. This digital marketing training needs to be carried out to make it easier for tourists who want to visit and stay at the Tuk-tuk Siadong hotel. This activity is carried out on Lake Toba which is located in the village of Tuk-tuk Siadong Regency. samosir and attended by employees and hotel management. In this activity an introduction was made to the RedDoorz application which emphasizes the what, why, and how if their hotel marketing is implemented digitally, as well as being a tourist attraction. So that tourists can easily find a place where they will stay. The stages of the method used in carrying out this activity are preparation, planning and implementation which are assisted by simpler methods, namely delivery of material, practice and discussion. The results obtained from this activity were around 90% of participants understood how using the RedDoorz application could improve their hotel marketing. The conclusion obtained from the socialization activity is that digital marketing training by utilizing the RedDoorz application can improve the economy of hotel and guest house owners, as well as increase visitors who can easily book the hotel..